Gender boardroom quotas: a survey of Malaysian corporate directors - Ku Ismail, Ku Nor Izah; Mustapa, Ifa Rizad; Abd Rahman, Intan Maiza; Abdullah, Shamsul Nahar (Universiti Malaysia Sarawak, 2019)
A number of countries have introduced gender boardroom quotas by which firms are required to appoint at least a certain number or proportion of women to their boards. Subsequently, the government of Malaysia, in 2011, introduced the policy of having at least 30 percent women on corporate boards. This study seeks the opinion of corporate directors on whether they are supportive of the policy. In addition, we examine if the characteristics of the respondents influence their opinion. A questionnaire survey was conducted on a sample of 84 directors who sit on the boards of listed companies in Malaysia. A majority of the respondents believe that there should not be any quota for both genders. Some of the respondents comment that it is not gender that matters; what is more important is the quality of individuals who sit on the board. We find that women are indifferent, while a majority of the men do not agree with the policy. In addition, directors who have a family relationship with any other directors tend not to favour the policy, compared to those who do not have any family relationship. We also find that a majority of the respondents do not agree that women directors could enhance firm financial performance and social responsibility activities; neither do a majority of them agree that women could curb unethical conducts. This study is important to the policymakers in that the results provide insights on the issue of whether the 30 percent quota is necessary.